Non-discrimination in the World Trade Organization : the rules and exceptions - Davey, William J., 1949- (Pocketbooks of the Hague Academy of International Law., 2012)
International trade is conducted mainly under the rules of the World Trade Organization. Its non-discrimination rules are of fundamental importance. In essence, they require WTO members not to discriminate amongst products of other WTO members in trade matters (the mostfavoured- nation rule) and, subject to permitted market-access limitations, not to discriminate against products of other WTO members in favour of domestic products (the national treatment rule). The interpretation of these rules is quite difficult. Their reach is potentially so broad that it has been felt that they should be li.